POPs paleoenvironmental record over the last 220 years from an ice core retrieved at the plateau site of Dome C, Antarctica - PIZZINI, Sarah; GREGORIS, ELENA; GAMBARO, Andrea; PIAZZA, Rossano (Swedish Chemical Society, 2017)
Persistent organic pollutants (POPs) are ubiquitous in the environment and are affected by long-range atmospheric transport (LRAT) due to their low vapour pressure. Therefore, these substances have been found in almost every environmental matrix worldwide, including the remote regions of Arctic and Antarctica [1-4]. Polar environments are almost free of local sources and are an ideal site for studying global contamination. Analyzing pollutants in ice cores can reveal the history of atmospheric transport and deposition, and can be useful for studying the variation of the sources over the years and the contribution of human activities to global pollution. In this work we obtained the POPs depth profile of a 16.5 m deep ice core (covering 212 years before present) drilled at the plateau site of Dome C, East Antarctica (75°06' South Latitude, 123°21' East Longitude), during the 23rd Italian Antarctic Expedition. Specifically, we analyzed 25 sections of the core investigating the presence of six classes of organic pollutants: polychlorinated biphenyls (PCBs), polychlorinated naphthalenes (PCNs), polycyclic aromatic hydrocarbons (PAHs), polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzo-p-furans (PCDFs) and polybrominated diphenyl ethers (PBDEs). The core covers a time interval which includes periods before and after the introduction of these POPs in commercial mixtures, as well as periods before the construction of research station facilities. Thus, the analysis of this core assumes considerable importance in assessing the impact of these choices to POPs global contamination. A recent paper investigated the presence of PCBs and PAHs in an ice core gathered at peripheral site GV7, Talos Dome, along the East Antarctic coast [3]. However, as to our knowledge this is the first study focusing on the simultaneous analysis of so many classes of POPs in an ice core, and this is the first analysis of organic pollutants in a core from the Antarctic plateau, which is the most remote area in the world. The ...